Wnt signaling during tooth replacement in zebrafish (Danio rerio): pitfalls and perspectives - Huysseune, Ann; Soenens, Mieke; Elderweirdt, Fien (Frontiers in Physiology, 2014)
The canonical (β-catenin dependent) Wnt signaling pathway has emerged as a likely candidate for regulating tooth replacement in continuously renewing dentitions. So far, the involvement of canonical Wnt signaling has been experimentally demonstrated predominantly in amniotes. These studies tend to show stimulation of tooth formation by activation of the Wnt pathway, and inhibition of tooth formation when blocking the pathway. Here, we report a strong and dynamic expression of the soluble Wnt inhibitor dickkopf1 (dkk1) in developing zebrafish (Danio rerio) tooth germs, suggesting an active repression of Wnt signaling during morphogenesis and cytodifferentiation of a tooth, and derepression of Wnt signaling during start of replacement tooth formation. To further analyse the role of Wnt signaling, we used different gain-of-function approaches. These yielded disjunct results, yet none of them indicating enhanced tooth replacement. Thus, masterblind (mbl) mutants, defective in axin1, mimic overexpression of Wnt, but display a normally patterned dentition in which teeth are replaced at the appropriate times and positions. Activating the pathway with LiCl had variable outcomes, either resulting in the absence, or the delayed formation, of first-generation teeth, or yielding a regular dentition with normal replacement, but no supernumerary teeth or accelerated tooth replacement. The failure so far to influence tooth replacement in the zebrafish by perturbing Wnt signaling is discussed in the light of (i) potential technical pitfalls related to dose- or time-dependency, (ii) the complexity of the canonical Wnt pathway, and (iii) species-specific differences in the nature and activity of pathway components. Finally, we emphasize the importance of in-depth knowledge of the wild-type pattern for reliable interpretations. It is hoped that our analysis can be inspiring to critically assess and elucidate the role of Wnt signaling in tooth development in polyphyodonts.